2015
DOI: 10.3945/jn.115.218982
|View full text |Cite
|
Sign up to set email alerts
|

Citrulline and Nonessential Amino Acids Prevent Fructose-Induced Nonalcoholic Fatty Liver Disease in Rats

Abstract: In our rat model, Cit and NEAAs effectively prevented fructose-induced NAFLD. On the basis of literature data and our findings, we propose that NEAAs may exert their effects specifically on the liver, whereas Cit presumably acts at both the hepatic and whole-body level, in part via improved peripheral Arg metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 45 publications
5
47
3
Order By: Relevance
“…There is evidence for citrulline as a key regulator in lipid metabolism, inflammation, and oxidative stress [68], [69], [70], [71]. In addition, studies support its role in skeletal muscle protein metabolism and its trophic effect on the gut [70], [72].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There is evidence for citrulline as a key regulator in lipid metabolism, inflammation, and oxidative stress [68], [69], [70], [71]. In addition, studies support its role in skeletal muscle protein metabolism and its trophic effect on the gut [70], [72].…”
Section: Discussionmentioning
confidence: 97%
“…In addition, studies support its role in skeletal muscle protein metabolism and its trophic effect on the gut [70], [72]. Recent findings indicate that citrulline may offer a therapeutic strategy for NAFLD [68], [69]. Citrulline is produced in the urea cycle mainly from ornithine and carbamoyl phosphate [73].…”
Section: Discussionmentioning
confidence: 99%
“…That the effect of arginine supplementation depends on prevailing arginine status could only be hypothesized from fragmented data in the literature. Some studies have shown that increasing arginine availability can restore cellular NO production and contribute to regulating the inflammatory process in situations of low plasma arginine concentrations (in diabetic obese rats or fructose-fed rats), reflecting impaired arginine metabolism (50,51). Similarly, there have been reports of improved NO synthesis after arginine supplementation in patients with sickle cell disease during a vasoocclusive crisis, when baseline plasma arginine concentrations are low (46 mmol/L) and characteristic of ''arginine deficiency'' states in other clinical conditions (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic intake of fructose increases DNL by activating several key transcription factors [12] such as Sterol Response Element Binding Protein 1c (SREBP1c) and Carbohydrate-Responsive Element-Binding Protein (ChREBP) [17,18]. As a consequence, their key target enzymes regulating lipid synthesis, such as Fatty Acid Synthase (FASN) and Acetyl-CoA Carboxylase (ACC), also increase as shown for example in rodents submitted to a 60% high fructose diet for eight weeks [18] or to a western diet where fructose is provided as a 30%-fructose containing beverage for eight weeks [19].…”
Section: Fructose and Hepatic Steatosismentioning
confidence: 99%
“…As a consequence, their key target enzymes regulating lipid synthesis, such as Fatty Acid Synthase (FASN) and Acetyl-CoA Carboxylase (ACC), also increase as shown for example in rodents submitted to a 60% high fructose diet for eight weeks [18] or to a western diet where fructose is provided as a 30%-fructose containing beverage for eight weeks [19]. …”
Section: Fructose and Hepatic Steatosismentioning
confidence: 99%